Ultrasound-Accelerated Permanganate Oxidation of Amines into Carbonyl Compounds - Thi, Luu Thi Xuan; Thach, Le Ngoc (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Potassium permanganate adsorbed on copper(II) sulfate pentahydrate has been found to be a green, efficient, and inexpensive oxidant for the transformation of amines into the corresponding ketones. The oxidation reactions were performed following two different activation methods: magnetic stirring, and ultrasound irradiation under the solvent-free or solvent conditions. Ultrasound irradiation made considerable influences on the heterogeneous reaction conversion and the product yield (> 55%) and reaction times (< 60 min).